Convective drying performance of porous moist objects under turbulent flow conditions: effects of object shape and material - Coban, Seda Ozcan; Selimefendigil, Fatih; Öztop, Hakan Fehmi (Emerald Group Publishing Ltd, 2022)
Purpose The purpose of this paper is to examine the coupled heat and mass transport of different shaped porous moist objects in a rectangular channel under the effects of convective drying. Numerical simulations were performed under turbulent conditions for cylindrical, triangular and rectangular shaped different food products in a two-dimensional channel. Design/methodology/approach Finite element method was used for the unsteady problem and, effects of drying air velocity (AV) and temperature on transport mechanism were evaluated. Three different food materials were used for the circular shaped object and drying performance of the products under different conditions was compared. Findings Results showed that, changing the air temperature has an important effect on drying for all shaped objects and all materials. The same effect was seen for the AV as, increasing the velocity had positive effects on drying. Two identical objects were placed in the channel one behind the other, and this configuration showed that location of the object in the channel is also important for drying. The moisture content in the object at the front is lower than in the object behind at the end of drying. Originality/value This paper can provide technical support to optimize drying performance in the industry with comprehensive data for the process.
Keywords: Convective drying; Coupled HMT; CFD; Multiphase flow